Sintesis dan Karakterisasi Cangkang Kapsul Non Gelatin dari Rumput Laut (Eucheumma cottonii) dan Kaktus Koboi (Cereus peruvianus) untuk Sistem Penghantaran Obat: Synthesis and Characterization of Non Gelatinized Capsule Shells from Seaweed (Eucheumma cottonii) and Koboi Cactus (Cereus peruvianus) for Drug Delivery Systems - Mahardika, Micha; Susparini, Ninik Triayu; Dewaldo, Dany; Situmeang, Boima; Amin, Fauzan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Research on drug delivery systems continues to develop, including making the latest formulations on capsule shells as a medium for drug delivery. The effort that has been done was developing non-gelatine drug delivery materials made from the combination of seaweed and cactus. The main component in making gel on seaweed and cactus is the polysaccharide pectin. This study aims to make and determine the characterization of capsule shells from a combination of seaweed and cactus. Capsule shells are made from a combination of pectin extracts from seaweed and cactus with 5 different ratios of 0:4 (A), 1:3 (B), 2:2 (C), 3:1 (D), and 4:0 (E). The characterization involved weight uniformity test, disintegration time test, water swelling test, and dissolution test. Pectin from green seaweed and koboi cactus weighed 235 g and 75 g. The capsule shell weights based on Farmakope Indonesia sixth edition were 307.2, 311.6, 309.7, 304.6, and 308.7 mg. The capsule shell disintegration times, based on Farmakope Indonesia sixth edition, 2020, were 15,16, 14, 21, and 12 minutes, and the best result of the water swelling test was C capsule (2:2) of 666.7%. The results of the capsule shell dissolution test showed that the reduction of the capsule shells did not exceed 10% for 30 minutes according to the Farmakope Indonesia sixth edition. The capsule shells made from a combination of seaweed and cactus can be used as material in drug delivery systems. Non-gelatinized capsule shell which is expected to have anti-inflammatory activity.